Exploring Moralitas Individual Mahasiswa, Sebuah Peran Mengatasi Etika Kecurangan Mahasiswa Akuntansi Di Dunia Pendidikan - Hertati, Lesi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2023)
The purpose of this research is to investigate the relationship between individual morality, regulations, and academic integrity and the ethics of cheating in accounting students. When accounting students' cheating ethics show decreasing grades, it causes a decline in educational power and accounting professional level. The factors that influence the ethical behavior of accounting students are very important. This research used a descriptive and descriptive approach, a survey was conducted on 250 accounting program students. The higher the individual morality of a student, the lower the possibility of accounting students being involved in academic cheating behavior. Ethics plays an important role in preventing accounting student fraud. The stronger the perception that students adhere to accounting ethics, the lower the level of fraud they commit. Accounting students' cheating ethics are related and those with high academic integrity tend to be more ethical in their academic and accounting behavior. The level of education that encourages academic integrity can play an important role in preventing accounting student fraud. The results of this study provide important insights for educators, accounting programs, and higher education institutions into ethics and reducing cheating among accounting students. If individual morality increases then strengthening regulations, as well as increasing academic integrity, in preparing students to become professionals in the field of accounting and ethical attitudes will play a role in the future.